2013
DOI: 10.1371/journal.pone.0070333
|View full text |Cite
|
Sign up to set email alerts
|

Increased DNA Damage in Progression Of COPD: A Response By Poly(ADP-Ribose) Polymerase-1

Abstract: Chronic oxidative stress (OS), a major mechanism of chronic obstructive pulmonary disease (COPD), may cause significant damage to DNA. Poly(ADP-ribose) polymerase (PARP)-1 is rapidly activated by OS-induced DNA lesions. However, the degree of DNA damage along with the evolution of COPD is unclear. In peripheral blood mononuclear cells of non-smoking individuals, non-obstructive smokers, patients with COPD of all stages and those with COPD exacerbation, we evaluated DNA damage, PARP activity and PARP-1 mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…We hypothesize that smoke-mediated activation of the parthanatos pathway of programmed cell death produces inflammation that if chronic, results in airway remodeling. Evidence for this is suggested by the finding that in COPD patients increasing PARP-1 activity correlates with disease severity 33 . Thus, smoke-mediated activation of the parthanatos pathway may represent one mechanism directly linking smoke exposure to the chronic inflammation of bronchial epithelia seen in smoking related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that smoke-mediated activation of the parthanatos pathway of programmed cell death produces inflammation that if chronic, results in airway remodeling. Evidence for this is suggested by the finding that in COPD patients increasing PARP-1 activity correlates with disease severity 33 . Thus, smoke-mediated activation of the parthanatos pathway may represent one mechanism directly linking smoke exposure to the chronic inflammation of bronchial epithelia seen in smoking related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with ours and others' findings that PARP-1 level is increased during CS-induced DNA damage [47] [51] , whereas conflicting results were obtained in other studies [52] , [53] . Nevertheless, the role of PARP-1 in DNA damage and repair during the pathogenesis of COPD is implicated [54] . A recent study has shown a physical association between p21 and PARP-1 [20] , implicating the regulation of p21-PARP-1 axis in CS-mediated DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pre-incubation of PBMCs with UPF17 (4-methoxy- l -tyrosinyl-a- l -glutamyl- l -cysteinyl-glycine), a novel tetra peptide analog of glutathione (GSH), strongly reduced mRNA expression of PARP-1 in patients with COPD as compared to non-obstructive individuals. Interestingly, in non-obstructive smokers, higher PARP-1 activity was found as compared to patients with mild COPD ( 183 ). Overall, these two studies conducted on human samples strongly suggest occurrence of systemic oxidative stress induced DNA damage and PARP-1 activation in COPD pathogenesis.…”
Section: Parp In Copdmentioning
confidence: 99%